Poverty, Inequality, the Middle Class in Iran - akram hamidian; aziz hazbavi; hasan reza yousefvand (توسعه اجتماعی)
Poverty and inequality, especially economic in equality has been addressed as one of the Iran's key problems. The aim of this study was to review the literature on poverty, inequality and justice and then utilized national and international reputable statistics to investigate trends in poverty and inequality in the past 25 years. Results showed that during this period the poverty and inequality both have been downward, but unemployment rate and misery index have in creased, total GDP per capita and GDP per persons employed haven’t increased, that means the economy has not improved, real Income of people didn’t increase and external increase of income due to governmental relief fund. Based on these result can say Iran's society go toward low middle class that there through governmental politics and monetary payment, income distribution are more equal and mean of income are more.